The Cambridge guide to pedagogy and practice in second language teaching - Richards, Jack C.; Burns, Anne, 1945- (Cambridge : Cambridge University Press, 2012)
'This collection of original articles provides a state-of-the-art overview of key issues and approaches in contemporary language teaching. Written by internationally prominent researchers, educators, and emerging scholars, the chapters are grouped into five sections: rethinking our understanding of teaching, learner diversity and classroom learning, pedagogical approaches and practices, components of the curriculum, and media and materials. Each chapter covers key topics in teaching methodology such as reflective pedagogy, teaching large classes, outcomes-based language learning, speaking instruction, and technology in the classroom. Chapters assume no particular background knowledge and are written in an accessible style'--
'As a consequence of the growing demand for effective English programs, language teaching professionals are engaged in a continual review and evaluation of their assumptions and practices. The emergence of approaches such as reflective teaching, task-based pedagogy, genre theory, and action research are examples of how the language teaching profession undergoes periodic waves of renewal and paradigm shifts as it continually reinvents itself through the impact of new ideas, new educational philosophies, new technology, and new research findings. The present volume seeks to document such changes through a comprehensive overview of current approaches and practices in language teaching'--
Machine generated contents note: Introduction Jack C. Richards and Anne Burns; Section 1. Rethinking our Understanding of Teaching: Introduction; 1. English as an international language Sandra Mckay; 2. Reflective pedagogy Kathleen M. Bailey; 3. Learner-centred teaching Phil Benson; 4. Class-centred teaching Rose Senior; 5. Competence and performance in language teaching Jack Richards; Section 2. Classroom Learning and Learner Diversity: Introduction; 6. Managing the classroom Tony Wright; 7. Learning strategies Christine C. M. Goh; 8. Motivation Ema Ushioda; 9. Teaching mixed level classes Jill Bell; 10. Teaching large classes Fauzia Shamim; 11. Teaching young learners Annamaria Pinter; 12. Teaching teenagers Michael K. Legutke; 13. Teaching adults Richard Orem; Section 3. Pedagogical Approaches and Practices: Introduction; 14. Task-based language education Kris Van den Branden; 15. Text-based teaching Anne Burns; 16. Content-based instruction and content and language integrated learning JoAnn (Jodi) Crandall; 17. Outcomes-based language teaching Constant Leung; 18. Teaching English for academic purposes Jean Brick; 19. Teaching English for specific purposes Brian Paltridge; 20. Literacy-based language teaching Richard Kern; Section 4. Components of the Curriculum: 21. Speaking instruction Scott Thornbury; 22. Listening instruction John Field; 23. Reading instruction Neil J. Anderson; 24. Writing instruction Dana Ferris; 25. Vocabulary instruction Anne O'Keeffe; 26. Pronunciation instruction Donna Brinton; 27. Grammar instruction Richard Cullen; Section 5. Media and Materials: Introduction; 28. Materials development Brian Tomlinson; 29. Technology in the classroom Mike Levy; 30. Online and bended instruction Hayo Reinders.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Foreign speakers; Second language acquisition -- Study and teaching